Post-abortion check-ups at Trento Family Planning Centre. Characteristics of those users who attended the check-up appointments and trends between 2003 and 2017 - Pertile, R.; Mazza, R.; Pedron, M.; Gurgone, P.; Piffer, S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The purpose of the study was to analyse the trend for post-abortion check-ups among users requesting the abortion certification from Trento Family Planning Center between 2003 and 2017. Study Design. Retrospective case-control study.Methods. During the study period, the Trento Family Planning Center issued a total of 3,870 abortion certificates (46% regarding foreign nationals). The social and demographic characteristics of those users who attended the post-abortion check-up appointments, and of those who did not, were compared. Results. The proportion of resident users who returned for a post-abortion check-up increases significantly during the study period. The multiple logistic regression analysis model indicates that the factors associated with the likelihood of a return for a post-abortion check-up are: possession of medium to high academic qualifications (> 8 years) versus low qualifications, being a non-EU or Asian citizen, being a minor and being nulliparous or multiparous versus primiparous.Conclusions. According to Family Planning Centers’ philosophy, post-abortion check-ups are a good opportunity for promoting responsible procreation. The strategy for the management of the Trento Family Planning Center’s users requesting an abortion led to an increase of the proportion of users who returned for the post-abortion check-up greater than is the case for other territorial Family Planning Centers.